2022
DOI: 10.1007/s00381-022-05649-7
|View full text |Cite
|
Sign up to set email alerts
|

Results of the treatment of pineal tumors in children: the Lyon experience

Abstract: Pineal tumors are rare and their incidence is of 1% among all pediatric tumors of the central nervous system. The survival depends on the histology, the extension of the surgical removal, the e cacy of the complementary treatment (chemotherapy and cranio-spinal irradiation) in relation with the age of the children.We report our experience in Lyon concerning 151 patients treated from 1997 to 2021. All patients were recorded in the French Register of Pineal tumors which is centralized in Lyon since 2010.The anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…However, pineal region lesions often have extensive tissue heterogeneity and mixed cell populations 14 . Most types of region lesions have a poor response to radiotherapy 15 . Moreover, we demonstrated that many pineal region lesions could not be completely removed with radiotherapy, even when the lesions were diagnosed as germinomas by neuroimaging, tumor markers, or plasma hormones.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…However, pineal region lesions often have extensive tissue heterogeneity and mixed cell populations 14 . Most types of region lesions have a poor response to radiotherapy 15 . Moreover, we demonstrated that many pineal region lesions could not be completely removed with radiotherapy, even when the lesions were diagnosed as germinomas by neuroimaging, tumor markers, or plasma hormones.…”
Section: Discussionmentioning
confidence: 80%
“…14 Most types of region lesions have a poor response to radiotherapy. 15 Moreover, we demonstrated that many pineal region lesions could not be completely removed with radiotherapy, even when the lesions were diagnosed as germinomas by neuroimaging, tumor markers, or plasma hormones. We believe that mixed tumors may be the reason for this phenomenon.…”
Section: Necessity Of Surgical Resection For Children With Pineal Reg...mentioning
confidence: 89%
See 3 more Smart Citations